Labor Augmentation with Oxytocin Decreases Glutathione Level - Naomi Schneid-Kofman; Tali Silberstein; Oshra Saphier; Iris Shai; Dorith Tavor; Ariela Burg (Obstetrics and Gynecology International)
Objective. To compare oxidative stress following spontaneous vaginal delivery with that induced by Oxytocin augmented delivery. Methods. 98 women recruited prior to labor. 57 delivered spontaneously, while 41 received Oxytocin for augmentation of labor. Complicated deliveries and high-risk pregnancies were excluded. Informed consent was documented. Arterial cord blood gases, levels of Hematocrit, Hemoglobin, and Bilirubin were studied. Glutathione (GSH) concentration was measured by a spectroscopic method. Plasma and red blood cell (RBC) levels of Malondialdehyde indicated lipid peroxidation. RBC uptake of phenol red denoted cell penetrability. SPSS data analysis was used. Results. Cord blood GSH was significantly lower in the Oxytocin group (2.3±0.55 mM versus 2.55±0.55 mM, 𝑃=.01). No differences were found in plasma or RBC levels of MDA or in uptake of Phenol red between the groups. Conclusion. Lower GSH levels following Oxytocin augmentation indicate an oxidative stress, though selected measures of oxidative stress demonstrate no cell damage.